2010
DOI: 10.1071/mf09060
|View full text |Cite
|
Sign up to set email alerts
|

Australian subtropical white syndrome: a transmissible, temperature-dependent coral disease

Abstract: Since 2000, a disease displaying white-syndrome characteristics has been observed affecting corals from the genus Turbinaria in the Solitary Islands Marine Park, New South Wales, Australia. Recently termed Australian subtropical white syndrome, this disease is transmissible through direct contact and by a predatory vector, but transmission through the water column has not been observed. In aquarium experiments, progressive tissue loss, extending from the region where healthy Turbinaria mesenterina fragments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 23 publications
0
47
0
Order By: Relevance
“…For example, in the Florida Keys, Hudson [64] treated black band disease (70% effective) by removing the pathogen by suction and covering the affected area with modeling clay (lesion occlusion). In Australia, Dalton et al [65] found that mechanical removal of the advancing disease margin for Turbinaria colonies affected by a tissue loss disease ("white syndrome") was successful at halting the disease in 80% of the colonies. AWS might be effectively managed by either lesion occlusion or mechanical removal of affected parts depending on the severity of the disease on the colony and the colony morphology.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Florida Keys, Hudson [64] treated black band disease (70% effective) by removing the pathogen by suction and covering the affected area with modeling clay (lesion occlusion). In Australia, Dalton et al [65] found that mechanical removal of the advancing disease margin for Turbinaria colonies affected by a tissue loss disease ("white syndrome") was successful at halting the disease in 80% of the colonies. AWS might be effectively managed by either lesion occlusion or mechanical removal of affected parts depending on the severity of the disease on the colony and the colony morphology.…”
Section: Discussionmentioning
confidence: 99%
“…These results differ from previous studies in which lesion removal was successful at stopping disease progression. Lesion removal halted white syndrome on Turbinaria mesenterina (Dalton et al 2010) and growth anomalies on Acropora acuminata (Dalton et al 2010, Williams 2013. The etiologies and ecologies of diseases differ, which affects the efficiency of any treatment method.…”
Section: Discussionmentioning
confidence: 99%
“…Similar treatment methods employing lesion removal have proven successful for mitigating the damage inflicted by certain coral diseases (Hudson 2000, Dalton et al 2010, Williams 2013, Aeby et al 2015. Removing pathogen-afflicted areas of tissue by suction and covering the affected area with modeling clay was 70% effective in controlling black band disease on affected Oscillatoria membrancea in the Florida Keys (Hudson 2000).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 2 more Smart Citations